PENGARUH EMISI OBLIGASI TERHADAP PENDAPATAN SEWA MODAL DENGAN PENDEKATAN MODEL DINAMIS AUTOREGRESSIVE PADA PT. PEGADAIAN (PERSER0) - Nurulhuda, Elly Soraya; Lutfiati, Anis; Purnama, Oktarian Trisna (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study aims to determine the effect of Bond Issuance Value on Capital Lease Income at PT. Pegadaian (Persero). The sample used in this research is the financial statements of PT. Pegadaian that issued bonds in 2007, 2009, 2011, 2012, 2013, 2014, 2015, 2017 and 2018. The independent variable of this study is the value of the bond issuance. The dependent variable is capital rental income. The analysis used is an autoregressive dynamic model with the Koyck approach. The results show that the value of bond issuance and capital lease income from the previous year has a significant effect on capital rental income.